Materialist Circuitry: Digital Writing Technology, Planned Obsolescence, and Ecological Impact - Madden, Shannon (My University, 2015)
This dissertation claims that planned obsolescence of digital writing equipment is a problem for composition—one that we should take up and challenge. Obsolescence causes practical difficulties for digital writing teachers and researchers because keeping up with the interfaces that are available and in use in public contexts can be troublesome and time consuming when those devices are so quickly changed, updated, and obsolesced. The project develops obsolescence as a heuristic and then uses obsolescence as a lens for analyzing the design of digital tools, ecological writing theory, and university digital initiatives. Through this analysis, I show that by studying obsolescence, we can see more clearly the forces shaping and reshaping writing practices. Bringing obsolescence into focus also helps us to consider the broader contexts in which writing tools circulate when they are not in our hands, and thus makes evident how our work is complicit with broader and sometimes geographically distant social issues.
Keywords: composition, rhetoric, literacy; digital technology; planned obsolescence; material rhetoric